1992
DOI: 10.1192/bjp.160.6.799
|View full text |Cite
|
Sign up to set email alerts
|

The Nithsdale Schizophrenia Surveys X: Obstetric Complications, Family History and Abnormal Movements

Abstract: Obstetric histories of 54 schizophrenic patients and 114 siblings were obtained from their mothers and scored using the Obstetric Complications Scale. There were no statistically significant difference in the proportion of schizophrenic patients (35%) and siblings (29%) who had at least one definite obstetric complication. There was no evidence that schizophrenic patients with a history of obstetric complications were less likely to have a first-degree relative with a history of psychiatric illness leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 25 publications
0
19
0
2
Order By: Relevance
“…Although some studies clearly attempted to use population-based methods (28,44,45,48), the final samples were selected to varying degrees and were prone to bias. Many studies relied solely on maternal recall as the source of information about the exposure (46,49,52). Subgroup analyses were common but yielded inconsistent results.…”
Section: Case-control Studies (1987-1997)mentioning
confidence: 95%
See 2 more Smart Citations
“…Although some studies clearly attempted to use population-based methods (28,44,45,48), the final samples were selected to varying degrees and were prone to bias. Many studies relied solely on maternal recall as the source of information about the exposure (46,49,52). Subgroup analyses were common but yielded inconsistent results.…”
Section: Case-control Studies (1987-1997)mentioning
confidence: 95%
“…Some studies found a significant overall effect for obstetric complications (44)(45)(46)(47)(48), others did not (49,50). Some studies had no normal comparison group (51)(52)(53), while others included a sibling comparison group (44,47,49,50,54). Different variations of the Lewis-Murray scale were used, but the results were still presented as total scores.…”
Section: Case-control Studies (1987-1997)mentioning
confidence: 96%
See 1 more Smart Citation
“…The association remains controversial due to both methodological weakness in the studies [31] and the failure to confirm the association in two historical cohort studies [37,38] and in one population-based case-control study [39]. Particular attention has been paid to the potential role of maternal recall bias in the case-control studies [37], although the association has also been found when original obstetric case notes have been examined.…”
Section: Discussionmentioning
confidence: 99%
“…[160][161][162] Sporadic cases are more likely to be winter-born 159,163,164 and have more electroencephalographic (EEG) abnormalities 153 and enlarged ventricles on CT scan or MRI. 152,165,166 Familial cases, on the other hand, have more neurological signs, 164,[167][168][169] poorer sustained attention performance; 170 cortical abnormalities on MRI 171 and reduced temporoparietal resting regional blood flow. 172 By and large, the F/S classification has not been successful in identifying homogeneous phenotype groups for genetic research.…”
Section: Subtypes Based On Putative Genetic Indicatorsmentioning
confidence: 99%